Kim possible (Los Angeles, California : Tokyopop, 2004)
"When it comes to two-stepping around danger, Kim Possible had evolved into a high-octane crime-stopping super-teen...but is she brave enough to ask the cutest boy to the school dance? with Drakken and Shego turning high-tech into crime-tech, it's up to Kim to stop the dastardly duo. And if that wasn't enough to drive her bananas, Monkey fist returns with an out-of-this-world scheme to become the ultimate monkey master!"--Cover.
At head of title: Disney's
Keywords: High school students -- Comic books, strips, etc